Pengaruh Maraknya Kasus Perceraian Public Figure Terhadap Pandangan Masyarakat Umum Tentang Pernikahan Dalam Hukum Islam - Pratama, Angga Adi (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
The divorce phenomenon that has occurred among artists in Indonesia recently has often been in the spotlight of netizens. In the virtual world and in the real world, divorce cases are a hot topic in Indonesian society today. The background to this research is the widespread news on social media about the phenomenon of female public figures, influencers or celebrities suing their husbands for divorce in court. There are various problems faced when living a married life, starting from cases of domestic violence, deviant behavior by the husband or wife, to infidelity. The method used by the author in this research uses qualitative research and library research, which emphasizes in-depth observation of a phenomenon which is then studied using scientific logic which refers to reading book literature, research journals, and statutory regulations, both Islamic law and law. positive. The research results explain that the impact of divorce, especially what happens to public figures, can cause various problems and negative impacts on those closest to them and people who receive information about the divorce. Views regarding the definition of marriage have become very complex due to the increasing number of divorce cases that occur.